An unblinded, randomised phase II study of platinum-based chemotherapy with vitamin B12 and folic acid supplementation in the treatment of lung cancer with plasma homocysteine blood levels as a biomarker of severe neutropenic toxicity. Issue 1 (11th December 2014) - Minchom, A R; Saksornchai, K; Bhosle, J; Gunapala, R; Puglisi, M; Lu, S K; Nimako, K; Coward, J; Yu, K C; Bordi, P; Popat, S; O'Brien, M E R
Abstract : Background: Vitamin B12 and folic acid (referred to as vitamin supplementation) improves the toxicity profile of pemetrexed containing regimens. Low baseline vitamin B12 and folate levels are reflected in a raised total homocysteine level (HC). Studies have suggested that pretreatment HC levels predict neutropenia toxicity. We have tested supplementation with vitamin B12 and folate in non-pemetrexed platinum-based regimens to decrease treatment-related toxicity and looked for a correlation between toxicity and change in homocysteine levels. Patient and method: Eighty-three patients with advanced lung cancer and malignant mesothelioma were randomly assigned to receive platinum-based chemotherapy with (arm A) or without (arm B) vitamin B12 and folic acid supplementation. The primary end point was grade 3/4 neutropenia and death within 30 days of treatment. Secondary end points included quality of life, overall survival (OS) and the relationship between baseline and post supplementation HC levels and toxicity. Results: In the intention-to-treat population, no significant difference was seen between the two groups with respect to chemotherapy-induced grade 3/4 neutropenia and death within 30 days of chemotherapy (36% vs 37%; p=0.966, emesis (2% vs 6%; p=0.9) or OS (12.3 months vs 7 months; p=0.41). There was no significant difference in survival rates by baseline HC level (p=0.9). Decrease in HC with vitamin supplementation was less frequent than expected. High baseline HC levels decreased with vitamin supplementation in only 9/36 (25%) patients (successful supplementation). Post hoc analysis showed that patients in arm A who were successfully supplemented (9/36=25%) had less neutropenic toxicity (0% vs 69%; p=0.02) compared to unsupplemented patients. Conclusions: The addition of vitamin B12 and folic acid to platinum-containing regimens did not overall improve the toxicity, quality of life or OS. Rates of grade 3/4 neutropenia at 36/37% was as predicted. Further studies to increase the rate of successful supplementation and to further test the biomarker potential of post supplementation HC levels in predicting chemotherapy-induced neutropenia in platinum-based chemotherapy are warranted. Trial registration number: EudracCT 2005-002736-10 ISRCTN8734355 .